DEVELOPMENT OF THE INTERNATIONAL AIR LAW IN THE LEAGUE OF NATIONS SYSTEM - Радзівілл, Олександр Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to show the International Air Law formation particularities, as a part of the new universal international-legal order under the aegis of the League of Nations. Methods of research: epistemological, comparative-historical, sociological and hermeneutic general-scientific and special methods. Results: the International Air Law codification important innovations have been shown, further determined in the practice of the international legal regulation at the universal level. Discussion: the problems of the multilevel sources of rule-making and the fragmentation of International Law issues solution should be based on the revealed by sociology regularities. The article shows the peculiarities of International Air Law formation at the beginning of the 20th century as a component of the first universal international law and order under the assistance of the League of Nations, formed as a response to fundamental social and geopolitical changes at the turn of the 19th-20th centuries. The intensification of attention to the experience of the formation of the Versailles-Washington system of international relations (the League of Nations system) is due to the existence of certain historical parallels between the transitional period of the 19th-20th centuries and the transitional period of the 20th-21st century. The tendency of the philosophical and political crises frequency on the verge of centuries is a kind of empirical generalization, at least for the history of societies that lead the chronology from AD. The more general trend is the periodic changes in the spontaneous and rational component of social processes: the attachment of crisis phenomena to the verge of centuries is due to the release of a human’s nature spontaneous component, where and when the value and ideological fundamentals on which the rational organization of public relations was based in the previous century, are critically revised, and new ones have not become a recognized factor in the solidarity of a society. This tendency, in its turn, is one of the manifestations of the phenomenon that is known in sociology under the title «self-fulfilling prophecies», when many individual expectations of certain events are combined in the «cooperative effect» of the mass mood, under the influence of which the expected events are implemented. Determined by the League of Nations fundamentals of the first universal international law and order organization remain to this day the constants of International Law. At the same time, in the light of the predominantly critical characteristics of their geopolitical dimension laid down by the efforts of diplomats substantially limited by the consciousness of the 19th century, the effective achievements of the International Air Law codification are out of the attention. Implemented for future cooperation, the Convention Relating to the Regulation of Aerial Navigation of October 13, 1919, adopted at the Paris Peace Conference, in the period between the two world wars ensured the rapid development of aviation at once on the level of international cooperation. The Convention with its annexes laid the fundamentals for multi-level air traffic regulation, involving in this process the rulemaking activity of other international institutions and bilateral agreements of the states, providing the legal basis for the regulation of private-law relations in the sphere of aviation communications.